Screening for Hepatopulmonary Syndrome in Cirrhotic Patients Using Technetium 99m-macroaggregated Albumin Perfusion Lung Scan (Tc-MAA): Diagnostic Approach and Clinical Correlations. Issue 9 (October 2018) - Fragaki, Maria; Sifaki-Pistolla, Dimitra; Samonakis, Dimitrios N.; Koulentaki, Mairi; Koukouraki, Sofia; Stathaki, Maria; Kouroumalis, Elias
Abstract : Background and Aims: The aims of this study were to prospectively screen cirrhotic patients with arterial blood gas test and albumin perfusion scan, identify those fulfilling the classic hepatopulmonary syndrome (HPS) criteria, correlate with clinical parameters, and evaluate the survival of patients with HPS compared with those without HPS in a genetically homogenous Cretan cirrhotic population. Materials and Methods: Data on consecutive 102 patients within 1 year were collected and analyzed. All patients underwent a technetium 99m-macroaggregated albumin perfusion lung scan (Tc-MAA). Diagnosis of HPS was based on the presence of the quantitative index Tc-MAA≥6% and a [P(A-a)O2 ]≥15 mm Hg (≥20 mm Hg for patients over >64 y). Results: In 94/102 patients, complete scintigraphic data were available. In total, 24 (26%) patients fulfilled the diagnostic criteria of HPS; 95.8% of them had mild-to-moderate HPS. In 8 patients the Tc-MAA scintigraphy could not be interpreted. There was no difference in HPS between decompensated (24.6%) and compensated cirrhosis (27.3%). In the multivariate analysis only the quantitative index was significant for the diagnosis of HPS ( P =0.001, odds ratio; 95% confidence interval, 7.05; 2.27-21.87). Kaplan- Meier survival curves indicated a similar overall prognosis for patients diagnosed with HPS ( P =0.105). Conclusions: HPS is a frequent complication of cirrhosis. Mild-to-moderate HPS has no significant effect on survival of cirrhotic patients. The quantitative Tc-MAA test is a reliable tool for diagnosis.